Angkasa Pura Digital Signage pada Bandar udara Syamsudinnor Banjarmasin - Hafizd, Khairul Anwar; Aolia, Melda (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2017)
Angkasa Pura Digital Signage at PT Angkasa Pura I (Persero) Syamsudinnor Airport Banjarmasin has used web application in inputting pictures and video, but information about schedule activity still done manually, that is done in writing. Therefore it is necessary to create an information system schedule activities, images, video and attendance using PHP employees who have previously been designed using ERD, DFD and Flowchart. The information system that has been created can input the schedule of activities, pictures, videos and attendance of employees displayed through digital signage or displayed through LCD or monitor screen.